Conflito e coordenaç\~ao federativa nos investimentos federais executados por municípios - Paulo de Tarso Fraz\~ao Linhares; Pedro Lucas de Moura Palotti; Roberto P. Messenberg (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– This Discussion Paper deals with the institutional and economic aspects of the Brazilian federative state according to the 1988 Constitution. The context of vertical coordination of urban infrastructure investments is then examined. Previous studies have shown that the benefits of economic efficiency in this type of investment between 2013 and 2015 - made possible by the Caixa Econômica Federal (CEF) intermediation and administration of federal resources - depended much on local institutional aspects of the federative coordination. Based on new evidence, the text examines the state of local execution of federal investment projects in the period 2015-2019. For this analysis, data gathered by the Tribunal de Contas da Uni\~ao (TCU) were used. The most recent performance of these projects is then evaluated vis-à-vis the performance of federal investments as a whole - and, particularly, vis-à-vis the performance of those projects listed in the (by now terminated) Programa de Aceleraç\~ao Econômica (PAC). Thus, the consequences of an altered state of federative coordination on the economic efficiency of local investments are inferred. It is concluded that technical difficulties and budget restrictions due to an altered state of federative coordination strongly impacted (in a comprehensive and differentiated way) the performance of investments carried out with federal resources. Finally, it is recommended to regularize the financing of recoverable projects and to seek improvements in vertical coordination for the successful local execution of investments financed with federal resources.
Keywords: E61; E65; H11; H54; H60; H70; H73; H77; 330; federalism; federative coordination; public investment; local governments